2022
DOI: 10.1029/2022gl099654
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variability in EMIRS Daytime Observations of Water Ice Clouds During Mars Aphelion‐Season

Abstract: Diurnal analyses of water ice cloud optical depths retrieved from thermal infrared spectra by the Emirates Mars Infrared Spectrometer showed changing cloud abundance throughout the Martian day. Observations began with the start of the Emirates Mars Mission science phase near the beginning of aphelion‐season in Mars Year 36 and included the prominent aphelion cloud belt (ACB) and orographic clouds in the vicinity of volcanoes. A midday minimum with higher morning and afternoon optical depths was typical for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…The diurnal variations for dust (component 1) and water ice cloud (component 2) described above can be compared against observations from other spacecraft. For water ice cloud, a minimum optical depth in the middle of the day with higher amounts near dawn and dusk has been noted previously in retrievals from, for example, the THEMIS instrument on Mars Odyssey (M. D. Smith, 2019), the PFS instrument on Mars Express (Giuranna et al, 2021), and the EMIRS instrument on the Emirates Mars Mission (Atwood et al, 2022). Giuranna et al (2021) also found dust optical depths to be higher during the day than at night, consistent with the diurnal variation observed for TIRS component 1.…”
Section: Dust Versus Water Ice Cloudssupporting
confidence: 62%
“…The diurnal variations for dust (component 1) and water ice cloud (component 2) described above can be compared against observations from other spacecraft. For water ice cloud, a minimum optical depth in the middle of the day with higher amounts near dawn and dusk has been noted previously in retrievals from, for example, the THEMIS instrument on Mars Odyssey (M. D. Smith, 2019), the PFS instrument on Mars Express (Giuranna et al, 2021), and the EMIRS instrument on the Emirates Mars Mission (Atwood et al, 2022). Giuranna et al (2021) also found dust optical depths to be higher during the day than at night, consistent with the diurnal variation observed for TIRS component 1.…”
Section: Dust Versus Water Ice Cloudssupporting
confidence: 62%
“…The low‐latitude aphelion season water ice cloud belt dominated the retrievals of clouds during this period with additional polar clouds appearing later in the season (Atwood et al., 2022). Water ice cloud optical depth in the aphelion cloud belt reached a maximum between L s = 100° and 120° and decreased significantly after L s = 130°.…”
Section: Resultsmentioning
confidence: 99%
“…That water vapor was observed to be transported equatorward during northern summer. Clear diurnal variations in atmospheric temperatures and water ice cloud opacity were evident in the retrievals (Atwood et al., 2022; Fan et al., 2022). Detailed analysis of these retrieval results, especially in conjunction with results obtained from the two other instruments on‐board EMM, the Emirates Exploration Imager (Jones et al., 2021) and the Emirates Mars Ultraviolet Spectrometer (Holsclaw et al., 2021), will improve our understanding of the underlying physical processes that operate in the current Mars atmosphere, while also helping to validate and tune general circulation models.…”
Section: Conclusion and Summarymentioning
confidence: 95%
See 1 more Smart Citation
“…In this paper, we focus solely on EXI observations, naturally limited to daytime hours. Observations by EMIRS are described by Atwood et al (2022); Smith et al (2022). We briefly describe the instrument, the data set, and the analysis algorithm.…”
mentioning
confidence: 99%